In-situ ethylene polymerization method for preparing high-performance polyvinyl-carbon fiber composite material
Through the use of diexic nickel fiber catalysts and carbon fiber modifiers in the ethylene polymerization reactions, the problem of lack of mechanical performance and chemical corrosion resistance of PE material through the in -situ polymerization polyethylene composite material through the original place. The preparation of high-performance polyethylene-carbon fiber composite materials.
Patent Information
- Application Number
- CN202411685112.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The mechanical properties and chemical corrosion resistance of existing PE materials are insufficient, making it difficult to meet the application scenarios that high performance requirements.
Trimine nickel compilations are used as catalysts for ethylene polymerization reactions, and carbon fiber is added during the ethylene polymerization process as modifiers, and polymerization modified polyethylene composite materials are legally synthetic.
The mechanical properties and chemical corrosion resistance of modified polyethylene composite materials are significantly improved, forming a new material with excellent pressure resistance, heat resistance and ductility.
Smart Images

Figure CN119331032A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a diimine nickel complex, a preparation method and application thereof in preparing a high-performance polyethylene-based-carbon fiber composite material by ethylene polymerization. Background Art
[0002] As one of the important varieties in the plastics industry, the output and market demand of polyethylene have maintained a rapid growth trend. According to statistics, the output of polyethylene accounts for about one-third of the world's total plastics. With the development of petrochemicals and the continuous emergence and application of new technologies, the production technology and product quality of polyethylene will be further improved and perfected. Polyethylene composites can significantly improve the strength and rigidity of the material by compounding with other materials (such as resins, fillers, etc.), so that it can meet application scenarios with higher performance requirements. Polyethylene materials themselves have good wear resistance, and composite materials can further enhance this property and extend the service life of the product. Polyethylene composites have good corrosion resistance to most chemicals such as acids, alkalis, and salts, and can maintain stable performance in harsh environments.
[0003] Carbon fiber is a high-strength, high-modulus fiber with a carbon content of more than 90%, mainly composed of carbon. It is an inorganic polymer fiber with excellent physical and chemical properties such as low density, high strength, high temperature resistance, high chemical stability, fatigue resistance, and friction resistance. In addition, carbon fiber also has good electrical and thermal conductivity, electromagnetic shielding, and low thermal expansion coefficient. It is low in price and has excellent performance. It is widely used in heavy industries such as aerospace, rail transportation, and vehicle manufacturing.
[0004] When preparing carbon fiber reinforced polyethylene composites, an interface bond is formed between the carbon fiber and the polyethylene matrix. Through appropriate process control, such as heat treatment, surface treatment, etc., this interface bond can be optimized so that the load can be transferred more effectively between the carbon fiber and the polyethylene matrix, thereby improving the overall strength of the composite material. Carbon fiber and polyethylene each have unique performance advantages. The high strength and high modulus of carbon fiber provide excellent load-bearing capacity, while polyethylene has good toughness and wear resistance. Combining the two together can give full play to their synergistic effect and form a new material with both high strength and good toughness. Summary of the invention
[0005] The technical problem to be solved by the present invention is how to improve the mechanical properties and chemical corrosion resistance of existing PE materials.
[0006] The present invention solves the above technical problems through the following technical means:
[0007] The present invention provides a diimine nickel complex, the structural formula of which is shown below:
[0008]
[0009] Preferably, the diimine nickel complex belongs to the orthorhombic system, the Pnma space group, and the unit cell parameter α=90°, β=90°, γ=90°.
[0010] Preferably, the diimine nickel complex is composed of an asymmetric diimine compound It is complexed with ethylene glycol dimethyl ether nickel bromide.
[0011] The present invention also provides a method for preparing the nickel diimide complex, comprising the following steps: The nickel diimide complex is obtained by reacting the nickel diimide complex with ethylene glycol dimethyl ether nickel bromide (DME) NiBr2 in dichloromethane at room temperature under an inert gas atmosphere, with a yield of more than 90%.
[0012] Preferably, the molar ratio of the ligand to ethylene glycol dimethyl ether nickel bromide is 1:1.
[0013] Preferably, the reaction is carried out under stirring conditions.
[0014] Preferably, the usage ratio of the asymmetric diimine compound to dichloromethane is 1 g:20 ml.
[0015] Preferably, the method for preparing the asymmetric diimine compound comprises the following steps:
[0016] S1. 4-methoxyaniline and tert-butyl substituted benzhydrol Friedel-Crafts reaction was carried out under the action of Lucas reagent to obtain the compound
[0017] S2. Compound and 2,3-butanedione As raw material, ketoamine condensation reaction occurs under the catalysis of acetic acid to obtain compound
[0018] S3, compound and 2,6-diisopropylaniline as raw materials, and a condensation reaction is carried out under the catalysis of p-toluenesulfonic acid to obtain the asymmetric diimine compound.
[0019] Preferably, in S1, the molar ratio of 4-methoxyaniline to tert-butyl-substituted benzhydrol is 1:2.1, the reaction temperature is 160° C., and the reaction time is 0.5 h.
[0020] Preferably, in S2, and 2,3-butanedione The molar ratio is 1:1, the reaction temperature is 80°C and the time is 24h.
[0021] Preferably, in S3, The molar ratio of 2,6-diisopropylaniline is 1:1.1, the reaction temperature is 140°C, and the reaction time is 12h.
[0022] The invention also provides an application of the diimine nickel complex as an ethylene polymerization catalyst.
[0023] Preferably, during the ethylene polymerization process, carbon fiber is also added as a modifier.
[0024] The present invention also proposes a method for preparing a modified polyethylene composite material using the diimine nickel complex as a catalyst, comprising the following steps: mixing a co-catalyst, a solvent and carbon fibers, adding a diimine nickel complex solution after degassing, and introducing ethylene for reaction to obtain the modified polyethylene composite material.
[0025] Preferably, the co-catalyst is Et2AlCl; the solvent is toluene; and the solvent of the diimine nickel complex solution is dichloromethane.
[0026] Preferably, the molar ratio of the co-catalyst to the diimine nickel complex is 400:1; the reaction pressure is 8.0 atmospheres, the temperature is 30° C., and the reaction time is 10 min.
[0027] The invention also provides a modified polyethylene composite material, which is prepared by a method for preparing the modified polyethylene composite material by using the diimine nickel complex as a catalyst.
[0028] The synthetic routes of the asymmetric diimine compound and the complex of the present invention are as follows:
[0029]
[0030] The advantages of the present invention are:
[0031] (1) The present invention, based on a novel asymmetric [N, N] nickel diimide catalyst, uses an in-situ polymerization method to synthesize a composite material. The asymmetry of the novel metal catalyst changes the active center structure and steric hindrance of the catalyst, thereby increasing the polymerization activity. The in-situ polymerization also enables the carbon fiber to be more fully and evenly filled into the polyethylene elastomer, thereby realizing a novel composite material with excellent compression resistance, heat resistance and ductility, and providing a new output path for the diversified development of polyolefin composite materials, and also providing a new way for the synthesis method of polyolefin composite materials.
[0032] (2) The present invention uses inorganic non-metallic carbon fibers as fillers when modifying PE materials, thereby preparing a new composite material with excellent mechanical properties.
[0033] (3) The carbon fiber and polyethylene used in the present invention each have unique performance advantages. The high strength and high modulus of the carbon fiber provide excellent load-bearing capacity, while the polyethylene has good toughness and wear resistance. The two can be combined to give full play to their synergistic effect to form a new material with high strength, good toughness and chemical corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The compound C of Example 1 of the present invention 1 H NMR spectrum;
[0035] Figure 2 The compound C of Example 1 of the present invention 13 C NMR spectrum;
[0036] Figure 3 is an X-Ray Crystallography image of compound D of Example 1 of the present invention;
[0037] Figure 4 This is a SEM scanning electron microscope image of the modified PE material obtained in Example 5 of the present invention;
[0038] Figure 5 The cyclic stress-strain curve of the modified PE material prepared in Example 2 of the present invention;
[0039] Figure 6 This is a physical picture of the modified PE material prepared in Example 2 of the present invention after being immersed in strong acid and strong alkali for 30 days;
[0040] Figure 7 It is the tensile diagram of the materials prepared from Examples 2-5 and Comparative Example 1 of the present invention (PE represents Comparative Example 1, CF-28%, CF-40%, CF-47%, CF-52% represent Examples 2-5 respectively). DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0043] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0044] The product performance test conditions of the following embodiments and comparative examples are as follows:
[0045] The tensile strength test used a tensile specimen model of (50.0±5.0)mm×(4.0±0.5)mm×(2.5±0.2)mm, with a tensile rate of 50mm / min;
[0046] The cantilever beam notched impact strength test uses a cantilever beam notched impact strength specimen with a model of (80.0±5.0)mm×(10.0±0.5)mm×(4.0±0.2)mm. The notch is machined with a milling machine, and the notch depth is (2.0±0.2)mm.
[0047] Example 1
[0048] Preparation of nickel diimide catalyst
[0049] Step (1): Synthesis of Compound A: Weigh 4-methoxyaniline (1.20 g, 10 mmol), tert-butyl-substituted benzhydrol (6.51g, 21mmol) was added to a pressure-resistant bottle and placed in an oil bath at 120°C. After the two solids were dissolved, zinc chloride solid (0.68g, 5mmol) was weighed and dissolved in 2ml of concentrated hydrochloric acid. The dissolved liquid was added to the pressure-resistant bottle and the oil bath temperature was adjusted to 160°C for stirring. When the temperature reached, the reaction was continued for 0.5h. After the reaction was completed, the mixture was cooled to room temperature, extracted three times with CH2Cl2, and dried with anhydrous magnesium sulfate. The magnesium sulfate was filtered out, the filtrate was concentrated, ethanol was added to precipitate the solid, and the desired product was obtained by drying in a vacuum drying oven. The reaction formula is as follows:
[0050]
[0051] Step (2): Synthesis of Compound B: Compound A (3.4 g, 5 mmol) and 2,3-butanedione (0.44 g, 5 mmol) were added to 50 ml of acetonitrile solution and placed in an oil bath at 80°C. After dissolution, 3 drops of acetic acid solution were added and reacted for 24 hours. The product after the reaction was concentrated, and recrystallized from a n-hexane solution to precipitate a solid. The product was dried in a vacuum drying oven to obtain the product. The reaction formula is as follows:
[0052]
[0053] Step (3): Synthesis of ligand C: Compound B (1.70 g, 2 mmol) and 2,6-diisopropylaniline (0.39 g, 2.2 mmol) were placed in a round-bottom flask, 100 ml of toluene solution was added, and the round-bottom flask was placed in an oil bath at 140°C, and a water separator and condenser were placed. After the drug was dissolved and refluxed for 15 min, 0.01 g of p-toluenesulfonic acid was added, and the reaction was continued under reflux for 12 h. The reactant was cooled to room temperature, concentrated, and recrystallized with n-hexane to obtain a bright yellow solid. After drying in a vacuum drying oven, the desired product C was obtained. The reaction formula is as follows: 1 H NMR spectrum, 13 C NMR spectrum Figure 1 , Figure 2 As shown;
[0054]
[0055] Among them, R 1 It is isopropyl.
[0056] Step (4): Synthesis of complex: Under nitrogen atmosphere, the compound C1g synthesized in step (3) was reacted with (DME)NiBr2 in CH2Cl2 (20 mL) solvent at room temperature (the molar ratio of compound C to (DME)NiBr2 was 1:1), the reaction time was 6 h, and the diimine nickel complex D with a diacetyl skeleton, i.e., diimine nickel catalyst, was synthesized after filtering, washing, and drying. The reaction formula is as follows:
[0057]
[0058] The X-Ray Crystallography of diimine nickel complex D is shown in Figure 3 As shown;
[0059] Bond length of diimine nickel complex D Sum bond angle (°): Br(1)-Ni(1)=2.3304(5), Br(2)-Ni(1)=2.3305(5), Ni(1)-N(1)=1.995(4), Ni(1)-N(2)=2.006(4), N(1)-C(29)=1.293(6) ), N(1)-C(32)=1.458(6), N(2)-C(23)=1.455(6), N(2)-C(28)=1.292(6); Br(2)-Ni(1)-Br(1)=119.94(3), N(2)-Ni(1)-Br(1)=11 2.28(4), N(2)-Ni(1)-Br(2)=112.28(4), N(1)-Ni(1)-Br(1)=112.48(4), N(2)-Ni(1)-Br(2)=112.48(4), N(1)-Ni(1)-N(2)=80.9 4(15), C(29)-N(1)-Ni(1)=114.8(3), C(32)-N(1)-Ni(1)=123.0(3), C(29)-N(1)-C(32)=122.2(4), C(28)-N(2)-Ni(1)=114.2(3),
[0060] C(28)-N(2)-C(23)=121.4(4), C(23)-N(2)-Ni(1)=124.4(3)
[0061] The main crystallographic data are described in the following table:
[0062]
[0063]
[0064] Example 2
[0065] Preparation of modified PE material: A 350mL thick-walled glass pressure vessel is loaded with the required amount of Et2AlCl (800μmol), toluene (28mL), a portion of carbon fiber with a mass of 0.5g and a magnetic stirrer in a glove box. Connect the pressure vessel to the high-pressure polymerization line and degas the solution. Use an oil bath to heat the container to 30°C and allow it to equilibrate for 5 minutes. Use a syringe to inject the nickel diimide catalyst (2μmol) in Example 1 above in CH2Cl2 (2mL) into the container. Under stirring, ethylene is introduced into the reaction vessel for pressurization and maintained at 8.0 atmospheres of ethylene. After 10 minutes, the container is vented and the polymer is precipitated in acidified ethanol (ethanol / concentrated hydrochloric acid = 50:1 (volume ratio) mixture) and dried at 50°C under vacuum for 24 hours. The polyethylene elastomer is obtained, that is, the modified PE material polymerized in situ. (Its cyclic stress-strain curve is shown in Figure 5As shown, the sample was tested 10 times in a cycle, with a maximum strain of 300% and a reciprocating stretch rate of 75.5%, indicating that it has excellent elastic properties)
[0066] Note: The chemical formula of the nickel diimide catalyst used in this example is
[0067] Example 3
[0068] Preparation of modified PE material: A 350 mL thick-walled glass pressure vessel is loaded with the required amount of Et2AlCl (800 μmol), toluene (28 mL), a 1.0 g portion of carbon fiber and a magnetic stirrer in a glove box. The pressure vessel is connected to a high-pressure polymerization line to degas the solution. The container is heated to 30°C using an oil bath and allowed to equilibrate for 5 minutes. The nickel diimide catalyst (2 μmol) in Example 1 above in CH2Cl2 (2 mL) is injected into the container using a syringe. Under stirring, the reaction vessel is pressurized with ethylene and maintained at 8.0 atmospheres of ethylene for 10 minutes, the container is vented, the polymer is precipitated in acidified ethanol (ethanol / concentrated hydrochloric acid = 50:1 (volume ratio)), and dried at 50°C under vacuum for 24 hours. The polyethylene elastomer, i.e., the modified PE material polymerized in situ, is obtained.
[0069] Example 4
[0070] Preparation of modified PE material: A 350 mL thick-walled glass pressure vessel is loaded with the required amount of Et2AlCl (800 μmol), toluene (28 mL), a 1.5 g portion of carbon fiber and a magnetic stirrer in a glove box. The pressure vessel is connected to a high-pressure polymerization line to degas the solution. The container is heated to 30°C using an oil bath and allowed to equilibrate for 5 minutes. The nickel diimide catalyst (2 μmol) in Example 1 above in CH2Cl2 (2 mL) is injected into the container using a syringe. Under stirring, the reaction vessel is pressurized with ethylene and maintained at 8.0 atmospheres of ethylene for 10 minutes, the container is vented, the polymer is precipitated in acidified ethanol (ethanol / concentrated hydrochloric acid = 50:1 (volume ratio)), and dried at 50°C under vacuum for 24 hours. The polyethylene elastomer, i.e., the modified PE material polymerized in situ, is obtained.
[0071] Example 5
[0072] Preparation of modified PE material: A 350mL thick-walled glass pressure vessel is loaded with the required amount of Et2AlCl (800μmol), toluene (28mL), a 2.0g portion of carbon fiber and a magnetic stirrer in a glove box. Connect the pressure vessel to a high-pressure polymerization line and degas the solution. Heat the container to 30°C using an oil bath and allow it to equilibrate for 5 minutes. Use a syringe to inject the nickel diimide catalyst (2μmol) in Example 1 above in CH2Cl2 (2mL) into the container. Under stirring, the reaction vessel is pressurized with ethylene and maintained at 8.0 atmospheres of ethylene for 10 minutes, then the container is vented and the polymer is precipitated in acidified ethanol (ethanol / concentrated hydrochloric acid = 50:1 (volume ratio) mixture) and dried at 50°C under vacuum for 24 hours. The polyethylene elastomer is obtained, that is, a modified PE material polymerized in situ. The modified PE material obtained under these conditions was observed by SEM scanning electron microscopy (such as Figure 4 ), and found that carbon fibers were more evenly incorporated into polyethylene elastomer under in situ polymerization.
[0073] Comparative Example 1 (without adding carbon fiber)
[0074] Preparation of comparative sample materials: A 350 mL thick-walled glass pressure vessel is loaded with the required amount of Et2AlCl (800 μmol), toluene (28 mL) and a magnetic stirrer in a glove box. The pressure vessel is connected to a high-pressure polymerization line and the solution is degassed. The vessel is heated to 30°C using an oil bath and allowed to equilibrate for 5 minutes. The nickel diimide catalyst (2 μmol) in Example 1 above in CH2Cl2 (2 mL) is injected into the vessel using a syringe. Under stirring, the reaction vessel is pressurized with ethylene and maintained at 8.0 atmospheres of ethylene and a temperature of 30°C for 10 minutes, then the container is vented and the polymer is precipitated in acidified ethanol (ethanol / concentrated hydrochloric acid = 50:1 (volume ratio) mixture) and dried at 50°C under vacuum for 24 hours. A polyethylene elastomer is obtained.
[0075] The modified PE materials with carbon fiber doping mass ratios of 0%, 28%, 40%, 47%, and 52% obtained in Examples 2-5 and Comparative Example 1 were analyzed. From the macroscopic morphology, the doping was very uniform. The SEM observation showed that ( Figure 4 ) found that carbon fibers were better doped in the gaps of polyethylene, indicating that the in-situ polymerization method enables the filler to be more evenly doped in polyethylene.
[0076] The prepared material was laminated into dumbbell-shaped specimens using a laminating machine for performance testing. The tensile and impact resistance test results are shown in Figure 7 The test results are shown in the following table:
[0077] Comparative Example 1 Example 2 Example 3 Example 4 Example 5 Fiber doping amount / % 0% 28% 40% 47% 52% Tensile strength(Mpa) 5.69 12.90 16.92 21.00 22.38 Elongation at break (%) 320 1120 830 795 870 Compatibility - excellent excellent excellent excellent
[0078] Example 6
[0079] Prepare solutions with a mass ratio of 10% H2SO4, 10% HCl, and 10% NaOH, respectively, put the modified PE material in Example 2 into the solution for 30 days, observe the phenomenon, and test the chemical corrosion resistance of the composite material. Figure 6 The test results and test pictures are: Figure 6 It can be seen that after immersion in 10% H2SO4, 10% HCl, and 10% NaOH solutions by mass ratio for 30 days, there were no obvious changes such as bubbles on the surface of the modified PE material, and a certain degree of integrity was maintained, indicating that the modified PE material has good chemical corrosion resistance in strong acids and alkalis.
[0080]
[0081] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A diimine nickel complex, characterized in that: Its structural formula is as follows:
2. The diimine nickel complex according to claim 1, characterized in that: It belongs to the orthorhombic system, Pnma space group, unit cell parameters α=90°, β=90°, γ=90°.
3. A method for preparing the diimine nickel complex as claimed in claim 1 or 2, characterized in that: The following steps are involved: Asymmetric diimide compounds As a ligand, in an inert gas atmosphere, it reacts with ethylene glycol dimethyl ether nickel bromide (DME) NiBr2 at room temperature in dichloromethane to obtain the diimine nickel complex.
4. The method for preparing the diimine nickel complex according to claim 3, characterized in that: The molar ratio of the ligand to ethylene glycol dimethyl ether nickel bromide is 1:
1.
5. Use of the diimine nickel complex as claimed in claim 1 or 2 as a catalyst for ethylene polymerization.
6. Use of the diimine nickel complex according to claim 5 as an ethylene polymerization catalyst, characterized in that: During the ethylene polymerization process, carbon fiber is also added as a modifier.
7. A method for preparing a modified polyethylene composite material using the diimine nickel complex as claimed in claim 1 or 2 as a catalyst, characterized in that: The following steps are involved: The co-catalyst, the solvent and the carbon fiber are mixed, and after degassing, a diimine nickel complex solution is added, and ethylene is introduced to react to obtain the modified polyethylene composite material.
8. The method for preparing a modified polyethylene composite material using a diimine nickel complex as a catalyst according to claim 7, characterized in that: The co-catalyst is Et2AlCl; the solvent is toluene; and the solvent of the diimine nickel complex solution is dichloromethane.
9. The method for preparing a modified polyethylene composite material using a diimine nickel complex as a catalyst according to claim 7 or 8, characterized in that: The molar ratio of the co-catalyst to the diimine nickel complex is 400:1; the reaction pressure is 8.0 atmospheres, the temperature is 30° C., and the reaction time is 10 minutes.
10. A modified polyethylene composite material, characterized in that: The polyethylene composite material is prepared by the method for preparing a modified polyethylene composite material using a diimine nickel complex as a catalyst as described in claim 8 or 9.
Citation Information
Patent Citations
Asymmetric benzhydryl alpha-diimine nickel complex, preparation and application thereof
CN104250270A
Asymmetric alpha-diimine nickel (II) complex for polymerizing ethylene and 1-hexene with o-benzhydryl substituent
CN107641138A
Tert-butyl asymmetric alpha-diimine nickel complex for preparation of ultrahigh-molecular-weight polyethylene elastomers and preparation method and application of tert-butyl asymmetric alpha-diimine nickel complex
CN108794545A
Fluorine-containing alpha-diimine nickel coordination compounds for preparing polyolefin elastomer, intermediate, preparation method and application thereof
CN111303215A